1 Kings : being good stewards of God's gifts. - Wiersbe, Warren W. (Colorado Springs, CO : David C. Cook, 2015)
This study of 1 Kings will remind you of the importance of moral character in leaders, as well as the tragedy of leaving God out of national affairs.
Introduction; Summary andReview.
Vendor-supplied metadata.
Master record variable field(s) change: 630
Keywords: Bible. -- Commentaries; Bible; RELIGION -- Biblical Studies -- Old Testament; Electronic books; Commentaries